Processos descivilizadores: Norbert Elias e o problema da violência no mundo civilizado - Souza, Carolina Batista de (2013)
This study is about the problem of violence on Norbert Elias’ civilizing process theory. It focuses on understanding how figurational sociology attempt to deal with criticisms through the concept of ‘decivilizing processes’. At the same time, it is demonstrated how this attempt develops a sociological explanation of the conditions leading into the emergence of Holocaust during Nazi Germany. In this way, it is discussed the consistency of Eliasian attempt to answering the question on the irruption of violence in the middle of the civilized world, its criticisms and its impacts on contemporary figurational sociology design.